Water-based coating for BOPP thermal composite pre-coating film, BOPP thermal composite pre-coating film and preparation method thereof
By using hyperbranched polyethylene-g-acrylic acid-acrylate copolymer and low-temperature heat sealed acrylic emulsion in aqueous coatings, the yellowing and adhesion problems of traditional BOPP thermal composite precoated films are solved, high adhesion and anti-adhesion, and the quality and production efficiency of composite products are improved.
Patent Information
- Application Number
- CN202411918012.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-25
- Publication Date
- 2025-04-01
- Estimated Expiration
- 2044-12-25
AI Technical Summary
Traditional BOPP thermal composite precoated films have yellowing defects caused by the use of AC agent to promote adhesion, and the storage of BOPP precoated film rolls is prone to adhesion in high temperature environments in summer.
Using an aqueous coating, including 40-70% hyperbranched polyethylene-g-acrylic acid-acrylate copolymer, 10-30% low-temperature heat sealed acrylic emulsion, 1-3% curing agent, 1-4% wetting agent, 0.1-2% defoaming agent and 10-30% water, the hyperbranched polyethylene-g-acrylic acid-acrylate copolymer is prepared by a specific preparation method, and the coated hot melt adhesive layer formed has high adhesion, anti-adhesion and good heat sealing strength.
The problem of yellowing and adhesion of the BOPP thermal composite precoated film is improved, the adhesion and thermal composite performance of the coated hot melt adhesive layer and the BOPP film are improved, and the quality and production efficiency of the composite product are ensured.
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of pre-coating films, in particular to a water-based coating for BOPP thermal composite pre-coating films, a BOPP thermal composite pre-coating film and a preparation method thereof. Background Art
[0002] BOPP film can usually be used as a composite film and used for composite processing with other materials (such as other plastic films, paper, metal foil, etc.) to form different composite products to meet different application requirements. For example, in one application of BOPP film, BOPP film is composited with nylon, PE, PET and other plastic films as a flexible packaging material; in another application of BOPP film, BOPP film is composited with paper and can be used for books, magazines, promotional posters and packaging boxes. These composite products play different roles (such as waterproof, wear-resistant, fold-resistant, chemical corrosion-resistant, etc.) with the help of the characteristics of the composite BOPP film.
[0003] At present, the composite processing methods of BOPP film and other materials are mainly divided into instant coating process and pre-coating process. The instant coating process refers to directly coating glue on the surface of BOPP film with other materials for composite when composite is needed, but this process will emit a large amount of organic solvents, which is easy to cause environmental pollution. The pre-coating process refers to pre-coating hot melt adhesive on the surface of BOPP film to form a BOPP thermal composite pre-coated film, and then using the BOPP thermal composite pre-coated film to thermally composite with other materials when composite is needed. This composite process does not require the use of glue, does not produce VOCs, is green and environmentally friendly, and reduces costs. It has become an important development direction for the composite processing of BOPP film and other materials.
[0004] The traditional processing method of BOPP thermal composite pre-coated film is to use a T-die to melt-extrude ethylene-vinyl acetate copolymer (EVA) resin and coat it on the surface of the BOPP film to form a coating hot melt adhesive layer on the surface of the BOPP film. In traditional BOPP thermal composite pre-coated films, in order to improve the adhesion between the coated hot melt adhesive layer and the BOPP film, AC agent is usually added to the EVA resin to promote the adhesion between EVA and BOPP film. However, the added AC agent itself will produce yellowing, and the free radicals generated by its yellowing will induce oxidative degradation of the EVA resin, resulting in yellowing. This causes the BOPP thermal composite pre-coated film to easily turn yellow after being stored for a period of time, resulting in color difference in the coating after the BOPP thermal composite pre-coated film is thermally composited with other materials in subsequent applications. In addition, due to the low melting point and large viscosity fluctuations of EVA, the coated hot melt adhesive layer is easy to soften and become sticky, resulting in the BOPP thermal composite pre-coated film being stored in a high temperature environment in summer. The film rolls of the BOPP thermal composite pre-coated film are easy to stick together, and the unwinding noise is loud during use, and even causes film breakage, film breakage, appearance defects and other problems, causing great inconvenience and loss during use. Summary of the invention
[0005] Based on this, the object of the present invention is to provide a water-based coating for BOPP thermal composite pre-coating film, a BOPP thermal composite pre-coating film and a preparation method thereof. The BOPP thermal composite pre-coating film obtained by coating the water-based coating for BOPP thermal composite pre-coating film on the surface of the BOPP film improves the yellowing defect of the film roll caused by the use of AC agent to promote adhesion of the traditional BOPP thermal composite pre-coating film, and the problem of easy adhesion of the BOPP pre-coating film roll during storage in a high temperature environment in summer, thereby meeting the high-end composite needs of BOPP film.
[0006] To achieve the above object, the present invention adopts the following technical solutions:
[0007] A water-based coating for a BOPP thermal composite pre-coating film comprises the following components by mass percentage: 40-70% of a hyperbranched polyethylene-g-acrylic acid-acrylate copolymer, 10-30% of an acrylic emulsion, 1-3% of a curing agent, 1-4% of a wetting agent, 0.1-2% of a defoaming agent, and 10-30% of water; wherein the acrylic emulsion is a low-temperature heat-sealing acrylic emulsion; the hyperbranched polyethylene-g-acrylic acid-acrylate copolymer comprises a hyperbranched polyethylene block and an acrylic acid-acrylate copolymer graft chain, wherein the mass proportion of the hyperbranched polyethylene block is 40-55%; the crystallinity of the hyperbranched polyethylene block is 8-15% and the melting point is 90-100° C.; the mass content of acrylic acid in the acrylic acid-acrylate copolymer graft chain is 48-60%; and the preparation method of the hyperbranched polyethylene-g-acrylic acid-acrylate copolymer comprises the following steps:
[0008] (1) Preparation of multifunctional hyperbranched polyethylene: catalyzing the copolymerization reaction of ethylene and silane-protected undecenol monomer under the action of pyridine amine nickel complex and MMAO (modified oligomethylaluminoxane) catalyst, adding ethanol to terminate the polymerization after a predetermined time, and obtaining a translucent elastomer after the reaction product is precipitated with ethanol; then treating the translucent elastomer with acidified ethanol or tetra-n-butylammonium fluoride solution to remove the protection of hydroxyl groups, thereby obtaining a multi-hydroxy hyperbranched polyethylene containing multiple hydroxyl groups, i.e., the multifunctional hyperbranched polyethylene;
[0009] (2) Preparation of multifunctional hyperbranched polyethylene RAFT agent: The polyhydroxy hyperbranched polyethylene is reacted with trithiocarbonate ( S -1-dodecyl- S '-(α,α'-dimethyl-α''-acetic acid)trithiocarbonate, DDAT) or chlorinated trithiocarbonate are introduced into RAFT functional groups through polymer esterification reaction to form multifunctional hyperbranched polyethylene RAFT agents;
[0010] (3) Preparation of hyperbranched polyethylene-g-acrylic acid-acrylate copolymer: using BPO as an initiator, polymerizing the multifunctional hyperbranched polyethylene RAFT agent and acrylic acid-acrylate copolymer to obtain the hyperbranched polyethylene-g-acrylic acid-acrylate copolymer.
[0011] The water-based coating for BOPP thermal composite pre-coating film of the present invention forms a coating hot-melt adhesive layer coated on the surface of the BOPP film, and has high adhesion to the BOPP film. The coating hot-melt adhesive layer formed by the water-based coating for BOPP thermal composite pre-coating film of the present invention has excellent storage anti-stickiness, is not easy to soften and become sticky in a high-temperature storage environment in summer, has good anti-aging stability, is not easy to yellow, and thus avoids the problem of film color difference.
[0012] The water-based coating for BOPP thermal composite pre-coating film of the present invention can improve the storage anti-stickiness of the coated hot melt adhesive layer formed by the water-based coating for BOPP thermal composite pre-coating film by adding the hyperbranched polyethylene-g-acrylic acid-acrylate copolymer prepared by a specific method, while improving the adhesion between the coated hot melt adhesive layer and the BOPP film, and also improving the heat sealing strength of the coated hot melt adhesive layer when thermally composited with other materials in subsequent applications. In the preparation method of the hyperbranched polyethylene-g-acrylic acid-acrylate copolymer: in step (1), pyridylamine nickel complex is used as the main catalyst and MMAO is used as the co-catalyst to catalyze the copolymerization reaction of ethylene and silane-protected undecenol monomer, and the pyridylamine nickel complex has a "chain walking" mechanism in the polymerization process of ethylene and silane-protected undecenol, so that a hyperbranched structure on the side chain can be formed in the reaction product; then, the polyhydroxy hyperbranched polyethylene (i.e., the multifunctional hyperbranched polyethylene) can be obtained by treating with acidified ethanol or tetra-n-butylammonium fluoride solution to remove the protection of the hydroxyl group. In step (2), the RAFT functional group is introduced into the polyhydroxy hyperbranched polyethylene through a polymer esterification reaction with a trithiocarbonate or a trithiocarbonate chlorinated with acyl chloride to form a multifunctional hyperbranched polyethylene RAFT agent, so as to create conditions for the RAFT polymerization process of step (3). In step (3), the hyperbranched polyethylene-g-acrylic acid-acrylate copolymer is synthesized by polymerizing the multifunctional hyperbranched polyethylene RAFT agent and acrylic acid-acrylate copolymer by RAFT solution polymerization using BPO as an initiator, so that the structure of the hyperbranched polyethylene-g-acrylic acid-acrylate copolymer has a hyperbranched polyethylene block and acrylic acid-acrylate copolymer grafted chain. The present invention limits the mass proportion of the hyperbranched polyethylene block in the hyperbranched polyethylene-g-acrylic acid-acrylate copolymer to 40-55%, which is beneficial to improving the storage anti-stickiness of the coated hot melt adhesive layer formed by the water-based coating for the BOPP thermal composite pre-coated film, and is beneficial to improving the adhesion between the coated hot melt adhesive layer and the BOPP film, and also improves the heat sealing strength of the coated hot melt adhesive layer when it is thermally composited with other materials in subsequent applications.
[0013] The present invention further defines that in the hyperbranched polyethylene-g-acrylic acid-acrylate copolymer, the hyperbranched polyethylene block (i.e., the polyhydroxy hyperbranched polyethylene obtained in step (1) of the preparation method) has a crystallinity of 8-15% and a melting point of 90-100°C, so that the hyperbranched polyethylene-g-acrylic acid-acrylate copolymer has excellent low-temperature heat sealing and storage anti-sticking properties, and improves the problem that the coated hot melt adhesive layer formed by the water-based coating for the BOPP thermal composite pre-coating film coated on the surface of the BOPP film is easy to soften and sticky under the high-temperature storage environment in summer. At the same time, the non-crystalline part in the hyperbranched polyethylene block has excellent wetting and permeability to the BOPP film, which can improve the adhesion of the coated hot melt adhesive layer to the BOPP film and has excellent adhesion, and also avoids the yellowing of the film roll during the storage period due to the use of AC agent to improve the adhesion of the coated hot melt adhesive layer of the existing BOPP thermal composite pre-coating film, which affects the color difference of the BOPP thermal composite pre-coating film in subsequent applications.
[0014] The present invention further defines the mass content of acrylic acid in the acrylic acid-acrylate copolymer graft chain (i.e., the acrylic acid-acrylate copolymer used in step (3) of the preparation method) in the hyperbranched polyethylene-g-acrylic acid-acrylate copolymer as 48-60%, thereby improving the adhesion between the coated hot melt adhesive layer formed by the water-based coating for the BOPP thermal composite pre-coating film and other materials (e.g., paper, metal foil, nylon), and increasing the heat-sealing strength of the coated hot melt adhesive layer with other materials in subsequent applications. In the acrylic acid-acrylate copolymer graft chain, from the perspective of the rigidity of the molecular chain, acrylic acid is a hard monomer, while acrylate is a soft monomer, and acrylic acid contains a hydrophilic carboxyl group. By defining the mass content of acrylic acid in the acrylic acid-acrylate copolymer graft chain as 48-60%, the T gIn the corresponding range, while improving the water dispersibility of the hyperbranched polyethylene-g-acrylic acid-acrylate copolymer, the storage anti-stickiness of the coated hot melt adhesive layer formed by the water-based coating for the BOPP thermal composite pre-coating film can also be enhanced. At the same time, by limiting the mass content of acrylic acid in the acrylic acid-acrylate copolymer graft chain to 48-60%, it is also possible to ensure that the content of the soft monomer (i.e., acrylic acid ester) in the acrylic acid-acrylate copolymer graft chain is within the corresponding range, and the compatibility of the hyperbranched polyethylene-g-acrylic acid-acrylate copolymer with the acrylic emulsion can be improved. If the mass content of acrylic acid in the acrylic acid-acrylate copolymer graft chain is too low, it is not conducive to improving the water dispersibility of the hyperbranched polyethylene-g-acrylic acid-acrylate copolymer, and it is not conducive to the storage anti-stickiness of the coated hot melt adhesive layer; if the mass content of acrylic acid in the acrylic acid-acrylate copolymer graft chain is too high, that is, the content of hard monomer is too high, it is easy to cause the coated hot melt adhesive layer to become brittle and cracked.
[0015] The acrylic emulsion is a low-temperature heat-sealing acrylic emulsion, which is similar to the acrylic acid-acrylate copolymer graft chain structure in the hyperbranched polyethylene-g-acrylic acid-acrylate copolymer, so that the coated hot melt adhesive layer formed by the water-based coating for BOPP thermal composite pre-coating film has good mechanical stability, avoiding the phase separation problem of the components in the water-based coating for BOPP thermal composite pre-coating film during the film-forming process. The low-temperature heat-sealing acrylic emulsion has excellent adhesion and toughness, and is easy to combine with polar substances. The formed coated hot melt adhesive layer not only has a fast heat-sealing response speed and high thermal sensitivity when thermally composited with other materials in subsequent applications, but can also adapt to less glue application (i.e., lower coating dry weight), lower heat-sealing temperature and shorter pressing time. It can be melted at a lower thermal composite temperature when used, and has good heat-sealing performance.
[0016] The water-based coating for BOPP thermal composite pre-coating film of the present invention can further chemically cross-link the low-temperature heat-sealing acrylic emulsion and the carboxyl group of the hyperbranched polyethylene-g-acrylic acid-acrylate copolymer by adding the curing agent, thereby improving the water resistance, cohesion and composite fastness of the coated hot melt adhesive layer formed by the water-based coating for BOPP thermal composite pre-coating film.
[0017] The water-based coating for BOPP thermal composite pre-coating film of the present invention uses a hyperbranched polyethylene-g-acrylic acid-acrylate copolymer and a low-temperature heat-sealing acrylic acid which both have good anti-sticking properties below the thermal composite temperature. After being coated on the surface of the BOPP film, the film roll of the obtained BOPP thermal composite pre-coating film has no problems of poor unwinding and adhesion during the subsequent thermal composite application process, thereby improving the quality of the composite product and enhancing the production efficiency.
[0018] Furthermore, in the preparation method of the hyperbranched polyethylene-g-acrylic acid-acrylate copolymer, the pyridineamine nickel complex is synthesized according to the method reported in the literature: Zai S, Liu F, Gao H, et al. Longstanding livingpolymerization of ethylene: substituent effect on bridging carbon of 2-pyridinemethanamine nickel catalysts[J]. Chemical Communications, 2010, 46(24): 4321-4323. Preferably, the pyridineamine nickel complex is prepared by using CH 2 Cl 2 Add in the form of solution.
[0019] Furthermore, in the hyperbranched polyethylene-g-acrylic acid-acrylate copolymer, the hyperbranched polyethylene block (i.e., the polyhydroxy hyperbranched polyethylene obtained in step (1) of the corresponding preparation method) has a number average molecular weight of 10,000 to 60,000, and a degree of branching of (55-68) / 1000C.
[0020] Furthermore, in the hyperbranched polyethylene-g-acrylic acid-acrylate copolymer, in step (1), the predetermined time in "after the polymerization is carried out for a predetermined time" can be determined by a person skilled in the art based on the number average molecular weight of the polyhydroxy hyperbranched polyethylene obtained in step (1), but the predetermined time is no longer than the deactivation period of the pyridylamine nickel complex and MMAO, and is preferably 0.5-1.5 hours.
[0021] Furthermore, in the preparation method of the hyperbranched polyethylene-g-acrylic acid-acrylate copolymer, in the multifunctional hyperbranched polyethylene RAFT agent, the number of RAFT functional groups of each hyperbranched polyethylene molecule is 5-10.
[0022] Furthermore, in the preparation method of the hyperbranched polyethylene-g-acrylic acid-acrylate copolymer, the acrylic acid-acrylate copolymer is at least one of a binary copolymer and a ternary copolymer, the binary copolymer is at least one of acrylic acid-ethyl acrylate (AA-EA), acrylic acid-butyl acrylate (AA-BA), methacrylic acid-butyl acrylate (MAA-BA), and acrylic acid-hydroxypropyl acrylate (AA-HPA); the ternary copolymer is at least one of acrylic acid-hydroxypropyl acrylate-butyl acrylate (AA-HPA-BA) and acrylic acid-hydroxypropyl acrylate-ethyl acrylate (AA-HPA-EA).
[0023] Furthermore, the acrylic emulsion is a low temperature heat seal acrylic emulsion. The acrylic emulsion is preferably Joncryl ® HSL 703, Joncryl ® HSL 9010, Joncryl ® HSL 9011, Joncryl ® HSL 9013, NeoCryl ® BT-36, NeoCryl ® FL-715, NeoCryl ® At least one of FL-711.
[0024] Furthermore, the curing agent is at least one of aziridine and isocyanate compounds.
[0025] Furthermore, the wetting agent is at least one of modified acrylic resin and modified silicone resin compounds.
[0026] Furthermore, the defoaming agent is at least one of silicone oils and polyether-modified organic silicon compounds.
[0027] The present invention also provides a BOPP thermal composite pre-coated film, comprising a coated hot melt adhesive layer and a BOPP film layer; the coated hot melt adhesive layer is formed by coating any of the above-mentioned aqueous coatings for BOPP thermal composite pre-coated films on the surface of the BOPP film layer; the BOPP film layer is a BOPP film.
[0028] Furthermore, the coating dry weight of the hot melt adhesive layer is 2.5-10 g / m 2 .
[0029] Furthermore, the thickness of the BOPP film layer is 10-25 μm.
[0030] The present invention also provides a method for preparing any of the above-mentioned BOPP thermal composite pre-coating films, comprising the following steps:
[0031] S1: preparing any of the above-mentioned water-based coatings for BOPP thermal composite pre-coating films;
[0032] S2: applying the water-based coating for BOPP thermal composite pre-coating film onto the surface of BOPP film by using a coating machine, and drying to obtain the BOPP thermal composite pre-coating film.
[0033] Furthermore, the drying method is: drying in an oven at 70-80° C. for 40-60 seconds. Through the above drying method, the water-based coating for BOPP thermal composite pre-coating film forms the coating hot melt adhesive layer on the surface of the BOPP film, thereby forming the BOPP thermal composite pre-coating film including a BOPP film layer composed of BOPP film and a coating hot melt adhesive layer formed by the water-based coating for BOPP thermal composite pre-coating film.
[0034] Compared with existing technology:
[0035] The water-based coating for BOPP thermal composite pre-coating film of the present invention uses a hyperbranched polyethylene-g-acrylic acid-acrylate copolymer and a low-temperature heat-sealing acrylic acid which both have good anti-sticking properties below the thermal composite temperature. After being coated on the surface of the BOPP film, the film roll of the obtained BOPP thermal composite pre-coating film has no problems of poor unwinding and adhesion during the subsequent thermal composite application process, thereby improving the quality of the composite product and enhancing the production efficiency.
[0036] The water-based coating for BOPP thermal composite pre-coating film described in the present invention meets the requirements of traditional mature industrial processes such as roller coating, spray coating, and scraper coating, and the method of use is simple and easy, and has strong practicality and commercial prospects; in addition, the coating hot melt adhesive layer formed by the water-based coating for BOPP thermal composite pre-coating film described in the present invention is a water-based coating, and the processing process has no volatile organic compound (VOC) emissions, no odor generation, and is green and environmentally friendly. DETAILED DESCRIPTION
[0037] In order to facilitate the understanding of the present invention, the present invention will be described more fully below. However, the present invention can be implemented in many different forms and is not limited to the embodiments described herein.
[0038] The invention provides a water-based coating for a BOPP thermal composite pre-coating film, which comprises the following components by mass percentage: 40-70% of a hyperbranched polyethylene-g-acrylic acid-acrylate copolymer, 10-30% of an acrylic emulsion, 1-3% of a curing agent, 1-4% of a wetting agent, 0.1-2% of a defoaming agent, and 10-30% of water.
[0039] The present invention takes a hyperbranched polyethylene-g-acrylic acid-acrylate copolymer in which the molecular weight of the hyperbranched polyethylene is 20,000 and the mass fraction of the hyperbranched polyethylene block is 40% as an example, and the specific preparation process is as follows:
[0040] All copolymerization reactions were carried out under strict oxygen-free and water-free conditions. A 250 mL reactor was replaced with ethylene gas for more than two times and then filled with ethylene gas to a pressure of 1.2 atm. A mixture of MMAO (12 mmol), 40 mL of trimethylsilyl chloride protected undecenol and anhydrous toluene (where the concentration of trimethylsilyl chloride protected undecenol was 0.1 mol / L) was added, stirred and balanced at -10 °C for about 30 min, and then CH 2 Cl 2 The polymerization was initiated by solution. After 1 hour of polymerization, ethanol was added to terminate the reaction, and the reaction product was precipitated by ethanol to obtain a translucent elastomer; then the translucent elastomer was treated in a large amount of acidified ethanol to remove the protection of the hydroxyl group, and the product was filtered, washed with ethanol, and dried in a vacuum to a constant weight to obtain a multifunctional hyperbranched polyethylene with a molecular weight of 20,000.
[0041] Add the multifunctional hyperbranched polyethylene prepared above into a 100 mL reactor, add 6 mL of anhydrous toluene, heat to 80 °C, stir until completely dissolved, add 0.04 mL of pyridine (acid absorber), and heat under N 2 The mixture was stirred for 10 min under atmosphere, and the freshly prepared acyl chloride DDAT toluene solution (obtained by acyl chloride reaction of DDTA) was slowly added dropwise. The addition was completed in about 30 min. The mixture was stirred at 80 °C for 3 h, and then precipitated in a large amount of methanol. The precipitate was dissolved in toluene and precipitated in methanol twice, and then dried at 35 °C in vacuum to constant weight. The obtained elastomer was a multifunctional hyperbranched polyethylene RAFT agent.
[0042] BPO (0.3 mg), the multifunctional hyperbranched polyethylene RAFT agent prepared above (the number of RAFT functional groups in each hyperbranched polyethylene molecule is 8), monomer AA-EA (0.25 g, AA accounts for 48wt%) and 2.5 mL of toluene / DMF (v / v: 9 / 1) mixed solvent were added to a Schlenk flask respectively. After three liquid nitrogen freeze-evacuation-thaw cycles, nitrogen protection was introduced, and the Schlenk flask was placed in a pre-set 70°C oil bath for polymerization. After 2 h, the Schlenk flask was immediately taken out and immersed in liquid nitrogen for cooling. The product was precipitated in a large amount of ether. The precipitate was dissolved in THF and precipitated in ether and the cycle was repeated twice. The solid obtained was a hyperbranched polyethylene-g-acrylic acid-acrylate copolymer, in which the mass fraction of the hyperbranched polyethylene block accounted for 45%, and the mass content of acrylic acid in the acrylic acid-acrylate copolymer graft chain was 48%.
[0043] In the following examples or comparative examples, the number average molecular weight and degree of branching of the hyperbranched polyethylene block in the hyperbranched polyethylene-g-acrylic acid-acrylate copolymer, the mass fraction ratio of the hyperbranched polyethylene block, the crystallinity and melting point of the hyperbranched polyethylene block, and the carboxyl content in the acrylic acid-acrylate copolymer graft chain can be conventionally adjusted by those skilled in the art according to the above preparation method, and will not be repeated here.
[0044] Example 1
[0045] This embodiment provides a water-based coating for BOPP thermal composite pre-coating film, comprising:
[0046] 70% hyperbranched polyethylene-g-acrylic acid-acrylate copolymer (wherein the number average molecular weight of the hyperbranched polyethylene block is 10,000, the branching degree is 55 / 1000C; the mass fraction of the hyperbranched polyethylene block is 40%; the crystallinity of the hyperbranched polyethylene block is 8.5%, the melting point is 90°C; the mass content of acrylic acid in the acrylic acid-acrylate copolymer graft chain is 50%), 10% acrylic emulsion (NeoCryl ® BT-36), 3% curing agent (aziridine), 3% wetting agent (acrylic resin wetting agent), 0.1% defoaming agent (polyether silicone defoaming agent), and 13.9% deionized water.
[0047] The present embodiment also provides a BOPP thermal composite pre-coated film, comprising a coated hot melt adhesive layer and a BOPP film layer; the coated hot melt adhesive layer is formed by coating the water-based coating used for the BOPP thermal composite pre-coated film of the present embodiment on the surface of the BOPP film layer; the BOPP film layer is a BOPP film.
[0048] This embodiment also provides a method for preparing a BOPP thermal composite pre-coating film, comprising the following steps:
[0049] S1: According to the mass percentage components of the water-based coating for BOPP thermal composite pre-coating film of this embodiment, the raw materials of each component are added into a constant temperature sealed high-speed stirring tank and stirred to obtain the water-based coating for BOPP thermal composite pre-coating film; wherein the stirring speed is 1500 rpm, the temperature is controlled at 30°C, and the stirring time is 4 hours;
[0050] S2: The water-based coating for BOPP thermal composite pre-coating film is coated on the surface of a 10 μm thick BOPP film by a coating machine using a gravure roller coating method; wherein the surface of the BOPP film has been previously subjected to an online corona treatment; the water-based coating is dried in an oven at a temperature of 70-80°C for 40-60s to form a BOPP thermal composite pre-coating film.
[0051] In the BOPP thermal composite pre-coated film of this embodiment, the dry weight of the coated hot melt adhesive layer is 2.5 g / m2 .
[0052] The BOPP thermal composite pre-coated film of this embodiment can be directly thermally composited with paper printed matter on a paper-plastic laminating machine under the conditions of 100° C., 10 MPa, and 60 m / min.
[0053] Example 2
[0054] This embodiment provides a water-based coating for BOPP thermal composite pre-coating film, comprising:
[0055] 40% hyperbranched polyethylene-g-acrylic acid-acrylate copolymer (wherein the number average molecular weight of the hyperbranched polyethylene block is 60,000, the branching degree is 65 / 1000C; the mass fraction of the hyperbranched polyethylene block is 55%; the crystallinity of the hyperbranched polyethylene block is 15%, the melting point is 99°C; the mass content of acrylic acid in the acrylic acid-acrylate copolymer graft chain is 60%), 30% acrylic emulsion (Joncryl ® HSL 703), 1% curing agent (isocyanate compound), 1% wetting agent (modified silicone resin wetting agent), 2% defoaming agent (silicone oil defoaming agent), and 26% deionized water.
[0056] The present embodiment also provides a BOPP thermal composite pre-coated film, comprising a coated hot melt adhesive layer and a BOPP film layer; the coated hot melt adhesive layer is formed by coating the water-based coating used for the BOPP thermal composite pre-coated film of the present embodiment on the surface of the BOPP film layer; the BOPP film layer is a BOPP film.
[0057] This embodiment also provides a method for preparing a BOPP thermal composite pre-coating film, comprising the following steps:
[0058] S1: According to the mass percentage components of the water-based coating for BOPP thermal composite pre-coating film of this embodiment, the raw materials of each component are added into a constant temperature sealed high-speed stirring tank and stirred to obtain the water-based coating for BOPP thermal composite pre-coating film; wherein the stirring speed is 1500 rpm, the temperature is controlled at 30°C, and the stirring time is 4 hours;
[0059] S2: The water-based coating for BOPP thermal composite pre-coating film is coated on the surface of 25 μm thick BOPP film by gravure roller coating using a coating machine; wherein the surface of the BOPP film has been previously subjected to online corona treatment; the water-based coating is dried in an oven at a temperature of 70-80°C for 40-60s to form a BOPP thermal composite pre-coating film.
[0060] In the BOPP thermal composite pre-coated film of this embodiment, the dry weight of the coated hot melt adhesive layer is 9 g / m 2 .
[0061] The BOPP thermal composite pre-coated film of this embodiment can be directly thermally composited with paper printed matter on a paper-plastic laminating machine under the conditions of 100° C., 10 MPa, and 60 m / min.
[0062] Comparative Example 1
[0063] This comparative example provides a water-based coating, comprising:
[0064] 80% hyperbranched polyethylene-g-acrylic acid-acrylate copolymer (wherein, the number average molecular weight of the hyperbranched polyethylene block is 10,000, the degree of branching is 55 / 1000C; the mass fraction of the hyperbranched polyethylene block is 40%; the crystallinity of the hyperbranched polyethylene block is 8.5%, the melting point is 90°C; the mass content of acrylic acid in the acrylic acid-acrylate copolymer graft chain is 50%), 3% curing agent (aziridine), 3% wetting agent (acrylic resin wetting agent), 0.1% defoaming agent (polyether silicone defoaming agent), and 13.9% deionized water.
[0065] The comparative example also provides a BOPP thermal composite pre-coated film, comprising a coated hot melt adhesive layer and a BOPP film layer; the coated hot melt adhesive layer is formed by coating the water-based coating of the comparative example on the surface of the BOPP film layer; the BOPP film layer is a BOPP film.
[0066] This comparative example also provides a method for preparing a BOPP thermal composite pre-coating film, comprising the following steps:
[0067] S1: According to the mass percentage components of the water-based coating for BOPP thermal composite pre-coating film of this comparative example, the raw materials of each component are successively added into a constant temperature sealed high-speed stirring tank and stirred to obtain the water-based coating for BOPP thermal composite pre-coating film; wherein the stirring speed is 1500 rpm, the temperature is controlled at 30°C, and the stirring time is 4 hours;
[0068] S2: The water-based coating is coated on the surface of a 10 μm thick BOPP film by a coating machine using a gravure roller coating method; wherein the surface of the BOPP film has been previously subjected to an online corona treatment; the water-based coating is dried in an oven at a temperature of 70-80° C. for 40-60 seconds to form a BOPP thermal composite pre-coated film.
[0069] In the BOPP thermal composite pre-coated film of this comparative example, the dry weight of the coated hot melt adhesive layer is 2.5 g / m 2 .
[0070] The BOPP thermal composite pre-coated film of this comparative example can be directly thermally composited with paper printed matter on a paper-plastic laminating machine under the conditions of 100° C., 10 MPa, and 60 m / min.
[0071] Comparative Example 2
[0072] This comparative example provides a water-based coating, comprising:
[0073] 80% acrylic emulsion (NeoCryl ® BT-36), 3% curing agent (aziridine), 3% wetting agent (acrylic resin wetting agent), 0.1% defoaming agent (polyether silicone defoaming agent), and 13.9% deionized water.
[0074] The comparative example also provides a BOPP thermal composite pre-coated film, comprising a coated hot melt adhesive layer and a BOPP film layer; the coated hot melt adhesive layer is formed by coating the water-based coating for the BOPP thermal composite pre-coated film of the comparative example on the surface of the BOPP film layer; the BOPP film layer is a BOPP film.
[0075] This comparative example also provides a method for preparing a BOPP thermal composite pre-coating film, comprising the following steps:
[0076] S1: According to the mass percentage components of the water-based coating for BOPP thermal composite pre-coating film of this comparative example, the raw materials of each component are successively added into a constant temperature sealed high-speed stirring tank and stirred to obtain the water-based coating for BOPP thermal composite pre-coating film; wherein the stirring speed is 1500 rpm, the temperature is controlled at 30°C, and the stirring time is 4 hours;
[0077] S2: The water-based coating for BOPP thermal composite pre-coating film is coated on the surface of a 10 μm thick BOPP film by a coating machine using a gravure roller coating method; wherein the surface of the BOPP film has been previously subjected to an online corona treatment; the water-based coating is dried in an oven at a temperature of 70-80°C for 40-60s to form a BOPP thermal composite pre-coating film.
[0078] In the BOPP thermal composite pre-coated film of this comparative example, the dry weight of the coated hot melt adhesive layer is 2.5 g / m 2 .
[0079] The BOPP thermal composite pre-coated film of this comparative example can be directly thermally composited with paper printed matter on a paper-plastic laminating machine under the conditions of 100° C., 10 MPa, and 60 m / min.
[0080] Comparative Example 3
[0081] This comparative example provides a BOPP thermal composite pre-coated film, which is a traditional BOPP thermal composite pre-coated film on the market, comprising a BOPP film layer and a coated hot melt adhesive layer arranged in sequence; wherein the coated hot melt adhesive layer comprises ethylene-vinyl acetate copolymer (EVA) and AC accelerator, and the coated hot melt adhesive layer is formed by melt-extruding the above components using a T-die head and coating them onto the BOPP film.
[0082] Performance Testing
[0083] The following performance tests were performed on the BOPP thermal composite pre-coated films of Examples 1-2 and Comparative Examples 1-3 respectively:
[0084] Anti-adhesive test: After the surface of the hot melt adhesive layer of the BOPP thermal composite pre-coated film of Examples 1-2 and Comparative Examples 1-3 was laminated with the surface of the BOPP film layer (i.e. rolled into a "film roll" to laminate the two surfaces of the BOPP thermal composite pre-coated film), it was pressed with a preheated iron block (P = 2.5 KPa), placed in an oven at a preset temperature of 45 ° C and heated for 1 hour, and the interlayer adhesion was tested using a DYNISCO D9407 bonding tester.
[0085] Coating adhesion test: According to the standard of GB 1720-1979 "Determination of paint film adhesion", the adhesion of the hot melt adhesive layer of the BOPP thermal composite pre-coated film of Examples 1-2 and Comparative Examples 1-3 was tested, where 100 / 100 represents no film removal, and 90 / 100 represents 10% film removal.
[0086] White cardboard / aluminum foil thermal composite peeling strength test: After the coated hot melt adhesive layer of the BOPP thermal composite pre-coated film of Examples 1-2 and Comparative Examples 1-3 was thermally composited with white cardboard and aluminum foil respectively, the test was performed using Method A in accordance with the standard of GB / T 8808 "Test method for peeling strength of plastic composite films".
[0087] Ozone fumigation aging test: According to GB 7762-03 "Ozone cracking resistance test for vulcanized or thermoplastic rubber", the thermal oxygen aging yellowing properties of the BOPP thermal composite pre-coated films of Examples 1-2 and Comparative Examples 1-3 were tested. The color difference ΔE, L, a, and b values of the film rolls were tested using a 3nhNR10QC colorimeter.
[0088] Please refer to Table 1 and Table 2 for the test results:
[0089] Table 1 Test results of anti-stickiness, coating adhesion and peeling force performance
[0090]
[0091] It can be seen from the test data in Table 1 that the coated hot melt adhesive layer of the BOPP thermal composite pre-coating film of Examples 1-2 of the present invention has good adhesion to the BOPP film layer; at normal storage temperature (<45°C), the coated hot melt adhesive layer of the BOPP thermal composite pre-coating film of Examples 1-2 has good anti-sticking effect, which well solves the problem that the coated hot melt adhesive layer of conventional BOPP thermal composite pre-coating film (such as the BOPP thermal composite pre-coating film of Comparative Example 3) is easy to soften and sticky under high temperature storage environment in summer, causing the film roll of BOPP thermal composite pre-coating film to stick.
[0092] In the BOPP thermal composite pre-coated film of Comparative Example 1, the water-based coating for forming the hot melt adhesive layer does not use the low-temperature heat-sealing acrylic emulsion. Although the hot melt adhesive layer of the BOPP thermal composite pre-coated film of Comparative Example 1 has good adhesion, the hot-composite peeling force of the hot melt adhesive layer of the BOPP thermal composite pre-coated film of Comparative Example 1 on white cardboard and aluminum foil is significantly reduced. Comparative Example 1 proves that the low-temperature heat-sealing acrylic emulsion used in the present invention has a good promoting effect on the bonding of polar materials.
[0093] In the BOPP thermal composite pre-coated film of Comparative Example 2, the water-based coating for forming the hot melt adhesive layer does not use the hyperbranched polyethylene-g-acrylic acid-acrylate copolymer. Although Comparative Example 2 can form a BOPP thermal composite pre-coated film, the hot melt adhesive layer has no adhesion to the BOPP film layer. Comparative Example 2 proves that the hyperbranched polyethylene molecular chain in the hyperbranched polyethylene-g-acrylic acid-acrylate copolymer used in the present invention has a promoting effect on the adhesion of the BOPP film layer.
[0094] The BOPP thermal composite pre-coating film of comparative example 3 is a traditional BOPP thermal composite pre-coating film, which has high interlayer bonding strength, that is, it is easy to cause the problem of adhesion. However, the hot melt adhesive layer coated on the BOPP thermal composite pre-coating film of the present invention has a good anti-adhesion effect, which well solves the problem that the conventional BOPP pre-coating film is easy to soften and become sticky during high temperature storage in summer, causing the BOPP pre-coating film roll to stick.
[0095] Table 2 Aging performance test results
[0096]
[0097] Note: According to the CIE (International Commission on Illumination) Lab color space introduction: L (brightness) axis represents black and white, 0 is black, 100 is white; a (red and green) axis, positive values are red, negative values are green, and 0 is neutral; b (yellow and blue) axis, positive values are yellow, negative values are blue, and 0 is neutral.
[0098] It can be seen from the test data in Table 2 that the coated hot melt adhesive layer of the BOPP thermal composite pre-coating film of Examples 1 and 2 of the present invention has good anti-yellowing ability, which effectively solves the color difference problem of the BOPP pre-coating film.
[0099] At the same time, the BOPP thermal composite pre-coated film of Comparative Example 3 (traditional BOPP thermal composite pre-coated film) showed obvious yellowing and excessive color difference. The data of Comparative Examples 1 and 2 proved that the coated hot melt adhesive layer of the present invention has good anti-aging stability and will not turn yellow or have excessive color difference.
[0100] The above embodiments only express several implementation methods of the present invention, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for ordinary technicians in this field, several modifications and improvements can be made without departing from the concept of the present invention, and the present invention is also intended to include these modifications and modifications.
Claims
1. A water-based coating for BOPP thermal composite pre-coating film, characterized in that: The composition comprises the following components by mass percentage: 40-70% of a hyperbranched polyethylene-g-acrylic acid-acrylate copolymer, 10-30% of an acrylic emulsion, 1-3% of a curing agent, 1-4% of a wetting agent, 0.1-2% of a defoaming agent, and 10-30% of water; wherein the acrylic emulsion is a low-temperature heat-sealing acrylic emulsion; the hyperbranched polyethylene-g-acrylic acid-acrylate copolymer comprises a hyperbranched polyethylene block and an acrylic acid-acrylate copolymer graft chain, and the mass proportion of the hyperbranched polyethylene block is 40-55%; the crystallinity of the hyperbranched polyethylene block is 8-15% and the melting point is 90-100° C.; the mass content of acrylic acid in the acrylic acid-acrylate copolymer graft chain is 48-60%; the preparation method of the hyperbranched polyethylene-g-acrylic acid-acrylate copolymer comprises the following steps: (1) Preparing a multifunctional hyperbranched polyethylene: catalyzing a copolymerization reaction of ethylene and a silane-protected undecenol monomer under the action of a pyridine amine nickel complex and an MMAO catalyst, and terminating the polymerization by adding ethanol after a predetermined time. The reaction product is precipitated with ethanol to obtain a translucent elastomer; then treating the translucent elastomer with an acidified ethanol or a tetra-n-butylammonium fluoride solution to remove the protection of the hydroxyl groups, thereby obtaining a multi-hydroxy hyperbranched polyethylene containing multiple hydroxyl groups, i.e., the multifunctional hyperbranched polyethylene; (2) preparing a multifunctional hyperbranched polyethylene RAFT agent: introducing RAFT functional groups into the polyhydroxy hyperbranched polyethylene and trithiocarbonate or chlorinated trithiocarbonate through a polymer esterification reaction to form a multifunctional hyperbranched polyethylene RAFT agent; (3) Preparation of hyperbranched polyethylene-g-acrylic acid-acrylate copolymer: using BPO as an initiator, polymerizing the multifunctional hyperbranched polyethylene RAFT agent and acrylic acid-acrylate copolymer to obtain the hyperbranched polyethylene-g-acrylic acid-acrylate copolymer.
2. The water-based coating for BOPP thermal composite pre-coating film according to claim 1, characterized in that: In the hyperbranched polyethylene-g-acrylic acid-acrylate copolymer, the number average molecular weight of the hyperbranched polyethylene block is 10,000-60,000, and the branching degree is (55-68) / 1000C.
3. The water-based coating for BOPP thermal composite pre-coating film according to claim 1, characterized in that: In the preparation method of the hyperbranched polyethylene-g-acrylic acid-acrylate copolymer, in the multifunctional hyperbranched polyethylene RAFT agent, the number of RAFT functional groups on each hyperbranched polyethylene molecule is 5-10.
4. The water-based coating for BOPP thermal composite pre-coating film according to claim 1, characterized in that: In the preparation method of the hyperbranched polyethylene-g-acrylic acid-acrylate copolymer, the acrylic acid-acrylate copolymer is at least one of acrylic acid-ethyl acrylate, acrylic acid-butyl acrylate, methacrylic acid-butyl acrylate, acrylic acid-hydroxypropyl acrylate, acrylic acid-hydroxypropyl acrylate-butyl acrylate, and acrylic acid-hydroxypropyl acrylate-ethyl acrylate.
5. The water-based coating for BOPP thermal composite pre-coating film according to claim 1, characterized in that: The acrylic emulsion is Joncryl ® HSL 703, Joncryl ® HSL 9010, Joncryl ® HSL 9011, Joncryl ® HSL9013、NeoCryl ® BT-36, NeoCryl ® FL-715, NeoCryl ® At least one of FL-711.
6. The water-based coating for BOPP thermal composite pre-coating film according to claim 1, characterized in that: The curing agent is at least one of aziridine and isocyanate compounds.
7. The water-based coating for BOPP thermal composite pre-coating film according to claim 1, characterized in that: The wetting agent is at least one of modified acrylic resin and modified silicone resin compounds; the defoaming agent is at least one of silicone oil and polyether modified silicone compounds.
8. A BOPP thermal composite pre-coating film, characterized in that: It comprises a coated hot melt adhesive layer and a BOPP film layer; the coated hot melt adhesive layer is formed by coating the water-based coating for BOPP thermal composite pre-coated film as described in any one of claims 1 to 7 on the surface of the BOPP film layer; the BOPP film layer is a BOPP film.
9. The BOPP thermal composite pre-coating film according to claim 8, characterized in that: The coating dry weight of the hot melt adhesive layer is 2.5-10g / m 2 ; The thickness of the BOPP film layer is 10-25μm.
10. A method for preparing a BOPP thermal composite pre-coating film according to claim 8 or 9, characterized in that: The following steps are involved: S1: preparing a water-based coating for BOPP thermal composite pre-coating film as described in any one of claims 1 to 7; S2: applying the water-based coating for BOPP thermal composite pre-coating film onto the surface of BOPP film by using a coating machine, and drying to obtain the BOPP thermal composite pre-coating film.
Citation Information
Patent Citations
Low-temperature heat-seal acrylic emulsion for coating and preparation method thereof
CN102850891A
HBPE (hyperbranched polyethylene) functionalized with terminal hydroxyl groups and preparation method thereof
CN104877054A